Hunter-gatherers in a Changing World - Reyes-García, Victoria; Pyhälä, Ail (Springer Nature, 2017)
This book compiles a collection of case studies analysing drivers of and responses to change amongst contemporary hunter-gatherers. Contemporary hunter-gatherers' livelihoods are examined from perspectives ranging from historical legacy to environmental change, and from changes in national economic, political and legal systems to more broad-scale and universal notions of globalization and acculturation. Far from the commonly held romantic view that hunter-gatherers continue to exist as isolated populations living a traditional lifestyle in harmony with the environment, contemporary hunter-gatherers - like many rural communities around the world - face a number of relatively new ecological and social challenges to which they are pressed to adapt. Contemporary hunter-gatherer societies are increasingly and rapidly being affected by Global Changes, related both to biophysical Earth systems (i.e., changes in climate, biodiversity and natural resources, and water availability), and to social systems (i.e. demographic transitions, sedentarisation, integration into the market economy, and all the socio-cultural change that these and other factors trigger).